Development of the Amorphous Solid Dispersion of Curcumin: A Rational Selection of Polymers for Enhanced Solubility and Dissolution - Memoona Ishtiaq; Sajid Asghar; Ikram Ullah Khan; Muhammad Shahid Iqbal; Syed Haroon Khalid (Crystals, 2022)
The goal of this investigation was to determine the effectiveness of hydrophilic polymers in preparing a solid dispersion to enhance the solubility and dissolution of poorly water-soluble drugs, such as curcumin. In order to prepare the solid dispersion, curcumin was uniformly distributed in the polymeric matrix of polyethylene glycol (PEG 6000), hydroxypropyl methyl cellulose (HPMC E5), polyvinyl pyrrolidine (PVP K30), and bovine serum albumin (BSA) using the kneading and solvent evaporation methods. The developed dispersion formulations were characterized for solubility, dissolution, Fourier transform infrared (FTIR), X-ray diffractometry (XRD), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC). Attaining enhanced physical stability with solubility is crucial in the selection of suitable polymer types and ratios. The optimized HPMC E5 and PVP based dispersion displayed 4.3 and 2.8 times greater solubility compared to the pure drug, respectively. The SEM also showed the optimized HPMC-based dispersion was smoother in comparison to the PVP-based dispersion. The XRD and DSC validated the successful modification of the crystal structure of curcumin resulting in the enhancement of its solubility and dissolution. In conclusion, the HPMC E5 formulation was the optimal candidate to create solid amorphous dispersions of curcumin, which might be employed as an effective delivery system.